2012
DOI: 10.4025/actasciagron.v34i4.14418
|View full text |Cite
|
Sign up to set email alerts
|

The effect of homeopathic preparations on the activity level of Acromyrmex leaf-cutting ants

Abstract: ABSTRACT. The effect of homeopathic preparations on the activities of the leaf-cutting ants Acromyrmex spp. was studied. A field experiment involving ant nests in six experimental areas was performed using a randomised complete block design. Within each block, every ant nest was considered to represent one repetition. The treatments consisted of the following: Belladonna homeopathic preparations of macerated or triturated Acromyrmex spp. adults, homeopathic preparations of macerated or triturated ant nest fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
3
5
0
Order By: Relevance
“…This would be like a pathogenetic illness and may have interrupted its development. An effect similar to that described is the study by Giesel et al, 25 where leaf-cutting ant colonies ( Acromyrmex spp.) were treated with homeopathic medicines and this caused an overall decrease in insect activities for 20 days after its application.…”
Section: Discussionsupporting
confidence: 81%
“…This would be like a pathogenetic illness and may have interrupted its development. An effect similar to that described is the study by Giesel et al, 25 where leaf-cutting ant colonies ( Acromyrmex spp.) were treated with homeopathic medicines and this caused an overall decrease in insect activities for 20 days after its application.…”
Section: Discussionsupporting
confidence: 81%
“…The preparation methodology of the centesimal Hahnemannian high dilution, 30 CH, among the evaluated preparations, was the most efficient in suppressing the foraging activity of A. laticeps anthills. This finding corroborates the work by Giesel et al (2012;2013), who reported that dynamized high dilution preparations, when used to reductione foraging by A. sexdens piriventris and Acromyrmex spp. leafcutter ants, has a greater effect when the preparation method utilizes the grinding of the raw material to produce biotherapeutic preparations at high dilutions.…”
Section: Discussionsupporting
confidence: 82%
“…control with Metarhizium anisopliae and Trichoderma viride ( López and Orduz 2003 ); compost made with animal manure, plant residues, molasses, yeast, and agricultural lime ( Chaves 2006 ); grain formulations incorporating plant and fungi extracts ( Herrera-Salazar 2009 ); and the control of Acromyrmex spp. with homeopathic preparations ( Giesel et al. 2012 ).…”
Section: Discussionmentioning
confidence: 99%